Cover Image, Volume 40, Issue 6. Issue 6 (20th November 2017) - Khajeh, Mostafa; Fard, Sahar; Bohlooli, Mousa; Ghaffari‐Moghaddam, Mansour; Khatibi, Ali
Abstract : The cover image, by Mostafa Khajeh et al, is based on the Original Article Extraction of caffeine and gallic acid from coffee by electrokinetic methods coupled with a hollow‐fiber membrane, DOI:10.1111/jfpe.12565 .